Customers’ online interaction experiences with fashion brands: e-information and e-buying - Loureiro, S. M. C.; Amorim, M. (E-business - state of the art of ICT based challenges and solutions, 2017)
Online platforms (such as websites, blogs, social networks, crowdsourcing) enable consumers to interact with companies and brands in new ways. This chapter is the first attempt to go further and analyse how perceived fashion website quality, social influence and recommendation, credibility, and experience influence fashion consumer behaviour, considering performance expectancy as the core element of online trust, satisfaction and word-of-mouth. The proposed model is tested in the context of the fashion industry. Data comprises a sample of generation Y users of fashion websites to get information and buy clothes. In order to collect data, convenience mall-intercept sampling (Lisbon city centre area) served to draw a broad cross-section of consumers. Researchers used tablets to be used by consumers to answer the online survey. The final sample consisted of 312 participants. The instruments employed were adapted from previous studies and pilottested with a group of master’s students to verify the clarity of meaning and comprehension. Findings reveal the stronger influence of perceived quality and experience on the performance expectancy. Performance expectancy, in turn, exercises a positive effect on satisfaction and word-of-mouth.